2015
DOI: 10.1101/gad.266650.115
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent modulation of Pol II CTD phosphatase SSUP-72 regulates alternative polyadenylation in neuronal development

Abstract: Alternative polyadenylation (APA) is widespread in neuronal development and activity-mediated neural plasticity. However, the underlying molecular mechanisms are largely unknown. We used systematic genetic studies and genome-wide surveys of the transcriptional landscape to identify a context-dependent regulatory pathway controlling APA in the Caenorhabditis elegans nervous system. Loss of function in ssup-72, a Ser5 phosphatase for the RNA polymerase II (Pol II) C-terminal domain (CTD), dampens transcription t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…SSUP-72 regulates tissue-and stage-specific expression of UNC-44L via use of the internal PAS2 Previously, we found that a novel nuclear protein SYDN-1 is required for UNC-44L expression in neurons, acting to inhibit SSUP-72 and a subset of pre-mRNA 3′ end processing factors (Chen et al, 2015). Consistent with these findings, sydn-1(0) mutants displayed greatly decreased expression of UNC-44L:: GFP in the nervous system and in the adult vulva.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…SSUP-72 regulates tissue-and stage-specific expression of UNC-44L via use of the internal PAS2 Previously, we found that a novel nuclear protein SYDN-1 is required for UNC-44L expression in neurons, acting to inhibit SSUP-72 and a subset of pre-mRNA 3′ end processing factors (Chen et al, 2015). Consistent with these findings, sydn-1(0) mutants displayed greatly decreased expression of UNC-44L:: GFP in the nervous system and in the adult vulva.…”
Section: Resultsmentioning
confidence: 99%
“…In C. elegans, the unc-44 ankyrin gene extends over 40 kb, and produces multiple mRNA isoforms that are terminated predominantly at three poly(A) sites (designated proximal PAS1, PAS2 and the distal PAS3) (Chen et al, 2015) (Fig. 1A, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations